Data from: Mortality and lamb body mass growth in free-ranging domestic sheep – environmental impacts including lethal and non-lethal impacts of predators - Mabille, Geraldine; Stien, Audun; Tveraa, Torkild; Mysterud, Atle; Brøseth, Henrik; Linnell, John D. C. (Zenodo, 2015)
The management and recovery of large predator populations in areas where human persecution has driven them to ecological extinction requires a solid understanding of the effects of both predation and food limitation on prey populations. We used 11 yr of data on reported losses among 17.3 million free-ranging sheep Ovis aries in the Norwegian farming industry to elucidate the relative roles of climate, vegetation characteristics, sheep densities, lamb body mass and densities of predators and alternative prey on the number of lambs and ewes lost on summer pastures. We first examined whether predator densities predicted autumn lamb body mass through possible impacts of predators on body growth (non-lethal effects) but found no evidence for such effects in our study system. This might be due to weak anti-predator behavioral responses in domesticated sheep. However, autumn lamb body mass was predicted by both sheep density and winter and spring weather conditions, probably through food availability. Losses of both lambs and ewes were positively and strongly related to the density of Eurasian lynx Lynx lynx, wolverine Gulo gulo and brown bear Ursus arctos. In addition, food availability and spring weather conditions were associated to losses of lambs, while precipitation in May predicted losses of ewes. There was little evidence for interaction effects of predator species on losses, suggesting that most of the effects of the predators were additive to each other. Given the strong effect of predator densities on sheep losses, we conclude that changing livestock husbandry practices towards a system that actively protects sheep and/or active management of predator densities may be necessary to reduce sheep losses where predators are recolonizing. Data at the county level The origin of the different variables is given in the article. The column headings refer to the variable names used in the article. The predator density is given per 1000 km2 and the roe deer density as the number of animal shot per 10 km2. ...